The focus group research handbook - Edmunds, Holly; American Marketing Association (Lincolnwood, Ill. : NTC Business Books, 1999)
'The Focus Group Research Handbook is a comprehensive guide to contracting with a market research vendor to create a customized focus group study for your business or organization. Author Holly Edmunds thoroughly explains and simplifies the methodology of focus group studies and comprehensively outlines the steps you need to follow to implement and then analyze focus group research. From designing research vendor questionnaires to selecting an effective moderator, from analyzing results to turning those results into workplace gains, this book will provide you with all the tools and tips you'll need to simplify the focus group process.'--Jacket.
Focus groups -- Designing a focus group study -- Facility issues -- Focus group moderation -- Focus group evaluation -- Pros and cons of doing it yourself -- Other focus group situations -- Ethics in focus group research.
At head of title : American Marketing Association.
Includes index.
Keywords: Focus groups -- Handbooks, manuals, etc